A review on fish oil extraction from fish by-product as sustainable practices and resource utilization in the fish processing industry - Muhamad Nor Iqmal Mamat,; Hafeedza Abdul Rahman,; Noorul Syuhada Mohd Razali,; Sharifah Salmah Syed Hussain,; Khairul Farihan Kasim,; Noor-Soffalina Sofian-Seng, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The fish processing industry generates significant by-products, such as viscera, skin, bones, and heads, which are valuable for producing food, medicinal products, energy, and industrial feedstock. Fish oil, rich in omega-3 polyunsaturated fatty acids like eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), is widely used in nutritional supplements and other applications. Among these by-products, fish viscera contain the highest concentration of oil, making them an ideal target for extraction due to their cost-effectiveness and environmental benefits. Extracting oil from fish by-product helps reduce environmental pollution and promotes sustainable practices by fully utilizing fish resources. This holistic approach contributes to waste reduction and resource efficiency in the fish processing industry. By incorporating sustainable principles into extraction processes - such as using environmentally friendly solvents, implementing efficient solvent recovery systems, and ensuring compliance with environmental regulations - companies can enhance the sustainability of their operations while extracting valuable components. As demand for fish-based food products rises, effective extraction of fish oil and fishmeal from by-products becomes increasingly important. Various extraction methods, including physical, chemical, and biological approaches, are essential for separating solids, oil, and water to recover valuable components like EPA and DHA. Optimizing these processes and combining different methods can achieve high concentrations of polyunsaturated fatty acids (PUFAs) in fish oil, ranging from 65% to 80%. Emphasizing maximum PUFA content highlights the potential to enhance the quality and nutritional value of fish oil extracted from by-products while advancing sustainability in the fish processing industry.